First‐Principles Study of 3d Transition Metal Atoms Doped Ni13 Cluster as Efficient Electrocatalyst for Nitrogen Reduction Reaction. Issue 12 (7th November 2021) - Song, Wei; Xi, Menghui; Guo, Yongliang; He, Chaozheng; Fu, Ling
Abstract: Ammonia (NH3 ), the source compound of all nitrogen‐containing chemicals, is not only an important energy storage intermediate and potential energy carrier, but also an essential nitrogen source in fertilizer production. Therefore, it is very essential for agriculture and food production. In recent years, electrocatalytic NH3 synthesis can be carried out under ambient condition, and clean electric energy can be used to activate nitrogen molecule, which is a technical route with great potential, so it is considered as a promising method. The key problem of electrocatalytic NH3 synthesis is to design electrocatalysts with high catalytic activity and selectivity. Herein, a series of 3d transition metal (TM = Sc−Zn) atoms doped Ni13 cluster as electrocatalysts for NH3 synthesis using density functional theory are designed, and the effects of different TM atoms and active centers on the catalytic performance and reaction mechanism of electrocatalytic NH3 are explored. The results screen out that Ni12 V cluster has the best catalytic effect, and the introduction of charges can further reduce the free energy barrier of the nitrogen reduction reaction and effectively inhibit the hydrogen evolution reaction. Abstract : The activation degree of N2 is preliminarily measured by the adsorption energy ( E ads ) and free energy (Δ G (N2 →*N2 )) of N2 adsorbed on Ni12 TM (TM = Sc−Zn) clusters.